2018
DOI: 10.1021/acs.jpcb.8b10568
|View full text |Cite
|
Sign up to set email alerts
|

Supercooling and Nucleation of Fatty Acids: Influence of Thermal History on the Behavior of the Liquid Phase

Abstract: Saturated fatty acids are an exceptionally important class of liquids, used in many consumer products and suggested as phase change materials (PCMs) for thermal energy storage, in part because they crystallize with minimal supercooling. Here we investigate fatty acid nucleation to understand why crystallization is so facile, as a step toward identifying potential mechanisms for the suppression of supercooling in other PCMs. We find that fatty acid supercooling can be induced only if the liquid is first heated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Motivated by earlier investigations of their liquid phase, 1−4 recently, we have established that saturated fatty acids exist in clusters in the liquid state. 5 We also showed that these clusters decrease in number and/or size on heating past a threshold temperature, and the cluster reduction correlates with the onset of subsequent supercooling of fatty acids which otherwise nucleate efficiently.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Motivated by earlier investigations of their liquid phase, 1−4 recently, we have established that saturated fatty acids exist in clusters in the liquid state. 5 We also showed that these clusters decrease in number and/or size on heating past a threshold temperature, and the cluster reduction correlates with the onset of subsequent supercooling of fatty acids which otherwise nucleate efficiently.…”
Section: Introductionmentioning
confidence: 58%
“…Molecular clusters exist within the liquid phase of saturated fatty acids, and these clusters can be eliminated/ diminished when the fatty acid is heated above a threshold temperature. 5 It is well known that fatty acids form dimers through head-to-head interactions in both the solid and liquid phases, as well as in some solutions. 2 One consideration is whether the observed change in clustering behavior corresponds to a change in the hydrogen bonding between fatty acid molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molten fatty acids were compatible with aluminum alloys, stainless steel, and polycarbonate, but not with copper, nickel or magnesium alloys, or with polypropylene, cast acrylic, type I PVC, silicone rubber, ABS plastic or nylon [96]. Under most conditions, fatty acids show little supercooling [98], and their volume change on melting is very small [96]. Thermal conductivities of fatty acids are low, typically 0.2 to 0.3 W m −1 K −1 in the solid state, and 0.1 to 0.2 W m −1 K −1 in the liquid [96].…”
Section: Other Practical Mattersmentioning
confidence: 93%